ChemInform Abstract: [(Pb6I8){Mn(CO)5}6] 2‐: An Octahedral (M6X8)‐Like Cluster with Inverted Bonding. Issue 25 (5th June 2015) - Wolf, Silke; Reiter, Kevin; Weigend, Florian; Klopper, Wim; Feldmann, Claus
Abstract: [bmim]2 [{PbMn(CO)5 }6 I8 ] is synthesized from a solution of PbI2 and Mn2 (CO)10 in [bmim][NTf2 ] (NTf2 : bis‐trifluoromethanesulfonimide) in a glass ampule at 130 °C for 20 d (about 20% yield).